2020
DOI: 10.3390/ijms21134580
|View full text |Cite
|
Sign up to set email alerts
|

Rounding up the Usual Suspects: Assessing Yorkie, AP-1, and Stat Coactivation in Tumorigenesis

Abstract: Can hyperactivation of a few key signaling effectors be the underlying reason for the majority of epithelial cancers despite different driver mutations? Here, to address this question, we use the Drosophila model, which allows analysis of gene expression from tumors with known initiating mutations. Furthermore, its simplified signaling pathways have numerous well characterized targets we can use as pathway readouts. In Drosophila tumor models, changes in the activities of three pathways, Jun N-terminal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 116 publications
(257 reference statements)
3
19
0
Order By: Relevance
“…Also found were numerous genes previously identified as targets of Yki-mediated transcriptional repression, including elav , eya , dac , and wg among others [ 52 , 53 ]. Overall, we found consistent agreement between Yki S168A -indcued transcriptional changes and those identified previously in wing discs using loss-of-function mutation in wts , the key Yki inhibitor [ 54 , 55 ], which share similar profiles with other epithelial tumor drivers, such as Ras and Notch [ 46 ].…”
Section: Resultssupporting
confidence: 88%
See 1 more Smart Citation
“…Also found were numerous genes previously identified as targets of Yki-mediated transcriptional repression, including elav , eya , dac , and wg among others [ 52 , 53 ]. Overall, we found consistent agreement between Yki S168A -indcued transcriptional changes and those identified previously in wing discs using loss-of-function mutation in wts , the key Yki inhibitor [ 54 , 55 ], which share similar profiles with other epithelial tumor drivers, such as Ras and Notch [ 46 ].…”
Section: Resultssupporting
confidence: 88%
“…Among the genes upregulated in Yki S168A discs were the well-established Hippo pathway targets myc , diap1, and ex (the yki transcript level was also highly upregulated as expected), consistent with UAS-mediated Yki overexpression [ 29 , 44 , 45 ]. Numerous additional genes implicated in Yki activity were also found, including kibra, cher, ftz-f1, jbug, sog, ilp8, merlin, sav, jub, wts, and tai [ 46 ]. Among the most highly upregulated genes was a group of BTB-zinc finger domain genes comprised of chinmo, fruitless, abrupt, and ken, as well as lola to a less significant degree.…”
Section: Resultsmentioning
confidence: 99%
“…These differences in cell lines and primary cells underscore the high complexity and (patho-) physiological variability of AP-1 effects in biological systems, which likely depend on: (i) the relative abundance of the different fos and jun components; (ii) the fine-tuned composition of the resulting AP-1 complexes; (iii) the functionally relevant, three-dimensional structure of these complexes; and (iv) their DNA binding and transactivation properties [ 7 , 14 , 42 ]. Whether crosslinks between the AP-1 pathway and other central signaling pathways [e.g., mitogen-activated protein kinases (MAPK; such as JNK, extracellular signal-regulated protein kinase (ERK), and p38), the phosphatidylinositide-3-kinase, and the Janus kinase/Signal transducer and activator of transcription (Jak/STAT) pathway [ 45 , 46 , 47 ]], known to be dysregulated in RA [ 46 , 48 ] and other diseases [ 49 , 50 ], contribute to the aforementioned differences, remains the focus of future studies.…”
Section: Discussionmentioning
confidence: 99%
“…Through decades of research, we have gained much knowledge on key molecular events and processes involved in the formation of cancer, and much of this knowledge has stemmed from investigations using model organisms, such as the mouse and the vinegar fly, Drosophila melanogaster, in addition to in vitro cell line studies. In this Special Issue, we present a collection of original research papers on various aspects of cancer research utilising human cell lines [7,8], or in vivo using Drosophila as a model system [9,10], as well as reviews highlighting the Drosophila model organism in cancer research [11][12][13][14][15]. Drosophila is a particularly useful model organism for the study of cancer mechanisms, because it has a rapid life cycle and is genetically manipulatable and since cancer genes and signalling pathways are highly conserved between humans and Drosophila, and interactions between tumour cells and surrounding normal cells can be readily examined in Drosophila tissues [6,[16][17][18][19][20].…”
mentioning
confidence: 99%
“…The identification of SF2 as a key conserved target of TORC1, which is required for early tumour growth in Drosophila, provides a potential new approach to develop anti-cancer therapies for tumours with upregulated TORC1 activity, such as those carrying loss of function of PTEN (phosphatase and tensin homolog deleted on chromosome ten) or constitutively active mutations in PI3K (phospho inositol 3 kinase) [23][24][25]. In a second research paper utilising the Drosophila model, Hamaratoglu and Atkins [10] undertook an analysis of published transcriptional data from various Drosophila imaginal disc epithelial cell models of cancer, and found that the JNK stress response pathway [26,27], and JAK/STAT [28,29], Hippo [30,31] and Notch [32,33] tissue growth signalling pathways are commonly deregulated. This important meta-analysis has opened-up new potential avenues of research to examine the cooperative interactions between these signalling pathways using model organisms, as well as to assess the co-dependency of these conserved pathways in human cancers.…”
mentioning
confidence: 99%